Suicide epidemiology in Italy: a population-based study in Piedmont Region. (13th November 2019) - Mamo, C; Coggiola, N; Dalmasso, M; Pitidis, A; Costa, G
Abstract: Background: Among the largest Italian Regions, Piedmont (Northern Italy) is the one with the highest rate of suicide. Aim of the study was to describe intentional self-harm related deaths in Piedmont analyzing trends by gender, age, area of residence, socio-economic level. Methods: Observational mortality study of the resident population in Piedmont from 2003 to 2014. Age-standardized rates of suicide (ICD-10: X60-X84) were estimated, by gender, health district of residence, mountain/level ground, and educational level. Suicide methods and places of occurrence by gender and age were inquired. Results: In a context of declining injury related mortality, especially for traffic accidents, the regional trend of suicides shows only a slight decrease, becoming the main cause of injury deaths since 2009, equal to 21% of all injury deaths in the studied period. There are no significant trend variations related to the period of economic crisis. The occurrence is higher among men in general and particularly in older people, persons with low educational level and those living in deprived areas. The main suicide method used by women is "jumping from a high place" (36.7%) while the main one for men is "hanging, strangulation and suffocation" (50%). This is globally the most frequent method for all ages. "Self-poisoning" gains importance between 30 and 49 years old. Suicides occur for over half of cases in home. Conclusions: Suicides are a public health and social concern. Yet despite its extent, this problem is still not adequately considered in public health prevention programs. Social and geographical gradients highlitght the importance to improve mental health service provision in deprived areas and to enhance public social welfare measures. Further contributions to a deeper understanding of the determinants of self-harm behaviour and suicidal risk can be obtained from health information systems, in particular data from Emergency Departments and multiple causes of deaths records. Key messages: In Italy, suicides are the main cause of injury deaths, without trend variations. Occurrence is higher among men, older people, persons with low educational level and those living in deprived areas.